2005
DOI: 10.4314/ejhd.v18i2.9946
|View full text |Cite
|
Sign up to set email alerts
|

A survey of bacteriological quality of drinking water in North Gondar

Abstract: Background: The high prevalence of diarrheal disease among children and infants can be traced to the use of unsafe water and unhygienic practices. The over all concept adopted for microbiological quality is that no water intended for human consumption shall contain E. coli in 100 ml sample. But, a 1-10 E.coli count per 100 ml is acceptable that needs regular sanitary checks for un chlorinated water. Objectives: To assess the extent of bacterial contamination among protected and unprotected water sources. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 2 publications
5
17
4
1
Order By: Relevance
“…The results of the bacteriological quality of water sources in this study concord with the results of other studies conducted in Africa [10][11][12] . The presence of significant counts of coliform bacteria in the water sources is indicative of inadequacy of the depth of the wells or a breach of sanitary integrity of the wells 13 .…”
Section: Discussionsupporting
confidence: 89%
“…The results of the bacteriological quality of water sources in this study concord with the results of other studies conducted in Africa [10][11][12] . The presence of significant counts of coliform bacteria in the water sources is indicative of inadequacy of the depth of the wells or a breach of sanitary integrity of the wells 13 .…”
Section: Discussionsupporting
confidence: 89%
“…According to Mengesha and his co-workers, research conducted in North Gonder, demonstrated that 50% of the samples had a coli form count of 180 and above /100 ml and the lowest coliform count was 13 coliform /100 ml (Mengesha et al, 2004), which is higher than the present study of Dire Dawa rural communities in which the highest total coliform 133.34 coliform /100 ml and the lowest total coliform 1.50 coliforms/100ml. In another study in South Wello, Ethiopia, Atnafu demonstrated that 75% of the samples from protected springs were contaminated with total coliforms (Atnafu, 2006).…”
Section: Table1: Bacteriological Analysis Of Unprotected Well Unprotcontrasting
confidence: 73%
“…High incidence of childhood diarrhea, helminthiasis, trachoma and the overall high mortality rates are associated with poor environmental sanitation (Mengesha et al, 2004). The World Health Organization estimated that up to 80% of all sicknesses and diseases in the world is caused by inadequate sanitation, polluted water or unavailability of water.…”
Section: Introductionmentioning
confidence: 99%
“…Water supplies and quality in Ethiopia are not different from the general situation of developing countries as a whole. The situation is worse in rural areas where coverage is only 20% when compared with 80% in urban areas which are the least among the continent (Admassu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%